2019
DOI: 10.2147/ott.s226921
|View full text |Cite
|
Sign up to set email alerts
|

<p>MiR-195-5p Inhibits Proliferation and Induces Apoptosis of Non-Small Cell Lung Cancer Cells by Targeting CEP55</p>

Abstract: Objective: This study aims to explore whether miR-195-5p can inhibit proliferation and induce apoptosis of non-small cell lung cancer (NSCLC) cells by targeting CEP55. Methods: qRT-PCR was used to measure the expression of miR-195-5p in NSCLC cells. MTT assay, colony formation assay, and flow cytometry were used to detect the role of miR-195-5p in NSCLC cells. Western blot was used to measure the protein expression of CEP55, Bax and Bcl-2 in cells. Dual-Luciferase assay was performed to verify the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 26 publications
2
52
0
Order By: Relevance
“…In ovarian cancer, overexpression of miR-195-5p can reduce cisplatin resistance and angiogenesis via PSAT1-depedent GSK3β/β-catenin signaling pathway [40]. To date, only four published papers have demonstrated the suppressive role of miR-195-5p in NSCLC cell proliferation and functioned as a predictor of poor prognosis [28][29][30][31]. In line with the published result, our further survival analysis proved that relatively low miR-195-5p expression was associated with unfavorable survival.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In ovarian cancer, overexpression of miR-195-5p can reduce cisplatin resistance and angiogenesis via PSAT1-depedent GSK3β/β-catenin signaling pathway [40]. To date, only four published papers have demonstrated the suppressive role of miR-195-5p in NSCLC cell proliferation and functioned as a predictor of poor prognosis [28][29][30][31]. In line with the published result, our further survival analysis proved that relatively low miR-195-5p expression was associated with unfavorable survival.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, miR-195-5p functions as a predictor of poor prognosis by directly targeting CIAPIN1 [30]. In addition, miR-195-5p Inhibited NSCLC cell proliferation and induced apoptosis by targeting CEP55 [31]. So we hypothesized whether miR-195-5p expression may be responsible for the differential expression among subtypes of lung cancer.…”
Section: Ivyspringmentioning
confidence: 97%
“…For mechanism analysis, circ_ZFR was identified to serve as the sponge for miR-195-5p and then elevated KPNA4 expression. Luo et al declared that miR-195-5p upregulation restrained cell growth, cell cycle and facilitated apoptosis in NSCLC cells via binding to CEP55 [ 27 ]. Zheng et al demonstrated the tumor suppressive role of miR-195-5p in NSCLC by regulating CIAPIN1 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-195 was reported to be downregulated in several cancers, and its overexpression could inhibit the proliferation and migration and regulate the G1/S transition of cancer cells in non-small cell lung cancer, breast cancer, and hepatocellular carcinoma. [52][53][54] In addition, miR-195-5p also acted as an anti-oncogene via targeting PHF19 in HCC. 54 CHEK1 was a serine/threonine-specific protein kinase mediating cell cycle arrest in response to DNA damage and functioned through the PLK-4/ATR/CHEK1 pathway in HCC.…”
Section: F I G U R Ementioning
confidence: 99%